Coronavirus Disease 2019 Emergency and Remote Eye Movement Desensitization and Reprocessing Group Therapy With Adolescents and Young Adults: Overcoming Lockdown With the Butterfly Hug - Lazzaroni, Elisa; Invernizzi, Roberta; Fogliato, Elisa; Pagani, Marco; Maslovaric, Giada (Frontiers in Psychology, 2021)
The Covid-19 pandemic has represented an individual and collective trauma with an impact on mental health. Restrictive measures such as lockdowns have increased risk factors for the development or triggering of various psychopathologies. Timely psychological intervention has constituted a protective factor that has been indicated as a form of prevention. The main objective of study was to measure changes in the levels of traumatic stress and anxiety in a clinical population of adolescents and young adults aged 13 to 24 years – already assisted by the local primary and specialty care services before the pandemic – following a trauma-focused psychotherapeutic group intervention according to the EMDR protocol, conducted remotely before the end of the first lockdown. The IES-R, STAI scales and the Emotion Thermometer were administered pre- and post-treatment. At the end of the treatment, the PTGI questionnaire on post-traumatic growth was administered. The results show that there was a significant improvement pre- and post-intervention in the scores of the scales STAI, IES-R and Emotion Thermometer with a reduction in post-traumatic symptoms related in particular to the domains of intrusiveness and hyperarousal. The domain of avoidance was less significantly modified by therapy. This overall clinical improvement did not correlate with any of the demographic variables of the sample. In addition, the results show a significant positive global perceived change (PTGI) that did not correlate with the reduction of anxiety or post-traumatic symptoms measured by the other self-report scales. The explored use of telemedicine has revealed a valuable clinical opportunity.